Analisis Peran Konselor Teman Sebaya dalam Mereduksi Perilaku Bullying pada Peserta Didik SMA Kota Ambon - Ellis, Rusnawati; Mahaly, Sawal; Korlefura, Criezta; Galib, Izatul Janah (Indonesian Journal of Counseling and Development, 2025)
The phenomenon of bullying in schools remains a serious issue that disrupts students' psychological and social development. Guidance and Counseling teachers often face limitations in reaching all cases, necessitating an additional strategy such as the implementation of peer counselors. This study aims to analyze the role of peer counselors in the effort to reduce bullying behavior among high school students in Ambon City. The research employed a descriptive quantitative approach, with 180 students from State High School (SMA) 3 and SMA 11 Ambon serving as the subjects. A purposive sampling technique was used for sample determination. Data were collected through a bullying behavior scale and analyzed descriptively. The results indicate that verbal bullying is the most dominant form (46.67%), followed by relational bullying (32.78%), physical bullying (12.78%), and cyberbullying (7.78%). The majority of students fall into the low-category of bullying behavior (85.6%), yet a small group is at high risk, thus requiring specific attention. Furthermore, the analysis of the peer counselors' role revealed their significant effectiveness in early detection of bullying cases and providing confidential and accessible support to both victims and perpetrators, thereby strengthening the school's overall anti-bullying efforts. These findings underscore the importance of empowering and optimizing the peer counselor program as a primary support system to create a safer and more inclusive school environment.